Case report: A choroidal fissure pial arteriovenous malformation inducing venous congestive edema of the medulla oblongata and cervicothoracic spinal cord presented with proximal arm predominant weakness - Jiang, Yun; Zhou, Ying; Yang, Ximeng; Sheng, Aizhen; Lu, Jun (Frontiers in Neurology, 2023)
Intracranial dural arteriovenous fistula (DAVF) can induce remote myelopathy via spinal perimeduallary venous drainage. Here we report a rare case of intracranial pial arteriovenous malformation (AVM) related myelopathy. A 52-year-old man presented with progressive, predominantly proximal weakness and muscle atrophy in bilateral upper limbs, urinary retention, and hyperreflexia in bilateral upper and lower limbs. Brain and cervicothoracic MRI showed longitudinal myelopathy extending from the medulla oblongata to T6 level with perimedullary enlarged veins from C1 to T12 level, and remarkable enhancement in bilateral anterior horns from C2 to C7 level. Cerebral angiography revealed a choroidal fissure AVM, which was supplied by the left anterior choroidal artery, drained exclusively by an inferior ventricular vein, descending toward the spinal perimedullary veins. After endovascular embolization of the feeding pedicle, nidus, and proximal segment of the draining vein, the patient’s neurological deficits rapidly improved and a significant recovery was achieved three months post-procedure. This rare case indicates that intracranial pial AVM can also cause extensive congestive myelopathy with similar mechanisms underlying intracranial and craniocervical DAVF cases, and grey matter in the spinal cord might be more susceptible to ischemia induced by intraspinal venous hypertension.